Translocation of tetrahedral DNA nanostructures through a solid-state nanopore. Issue 13 (18th March 2019) - Zhao, Xinjia; Ma, Ruiping; Hu, Ying; Chen, Xiaoyu; Dou, Ruifen; Liu, Ke; Cui, Chengjun; Liu, Huajie; Li, Qian; Pan, Dun; Shan, Xinyan; Wang, Lihua; et al.
Abstract : Translocation of tetrahedral DNA nanostructures (TDNs) and TDNs bonded to linear DNA molecules through a nanopore was first demonstrated. Abstract : Tetrahedral DNA nanostructures (TDNs) are programmable DNA nanostructures that have great potential in bio-sensing, cell imaging and therapeutic applications. In this study, we investigate the translocation behavior of individual TDNs through solid-state nanopores. Pronounced translocation signals for TDNs are observed that are sensitive to the size of the nanostructures. TDNs bound to linear DNA molecules produce an extra signal in the ionic current traces. Statistical analysis of its relative temporal position reveals distinct features between TDNs bound to the end and those bound to the middle of the linear DNA molecules. A featured current trace for two TDNs bound to the same linear DNA molecule has also been observed. Our study demonstrates the potential of using TDNs as sensitive bio-sensors to detect specific segments of a single DNA molecule in real time, based on solid-state nanopore devices.